Implementasi Penerapan Customer Relationship Management (CRM) Online untuk Meningkatkan Layanan Pendidikan terhadap Wali Murid di Sekolah Menengah Kejuruan - Fitria, Nur; Hidayat, Nurdin (Lentera: Jurnal Ilmiah Kependidikan, 2024)
Implementation of Online Customer Relationship Management (CRM) to Improve Educational Services for Parents of Students in Vocational High Schools, is research that implements an online program in the form of Whatsapp services and websites in order to improve and improve services for parents of students in Schools. CRM itself is actually often used in business companies, but is also starting to be used in the world of education. CRM aims to improve relationships with customers, in this case parents, and increase interest in the school, which ultimately results in the school having many students.  The online CRM used is an Android application in the form of a Whatsapp application and website. With this service application, parents of students can find out about the distribution of information and developments in school programs that will be and have been implemented for their children or students at the school, so that they can improve services that ultimately increase interest. Today a good customer relationship management (CRM) platform is the backbone of many successful student recruiting efforts. CRM for schools is a customer-centric system that can help education professionals, build relationships with prospects and enrollees, generating data-based insights.